Ліцензування будівельної діяльності – дієвий засіб державного регулювання - Лилов, О. В.; Дмитренко, В. І. (Ways to Improve Construction Efficiency, 2014)
The article analyzes the state regulation on licenses in construction. The main types of construction activities subject to compulsory licensing in Ukraine and stages of the process of obtaining a building permit. Characterized by positive and negative aspects of licensing of construction activity.